2015
DOI: 10.4238/2015.december.29.36
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional analysis of a chitin synthase gene (HcCS1) identified from the freshwater pearlmussel Hyriopsis cumingii

Abstract: ABSTRACT. The triangle sail mussel, Hyriopsis cumingii, is the most important freshwater pearl mussel in China. However, the mechanisms underlying its chitin-mediated shell and nacre formation remain largely unknown. Here, we characterized a chitin synthase (CS) gene (HcCS1) in H. cumingii, and analyzed its possible physiological function. The complete ORF sequence of HcCS1 contained 6903 bp, encoding a 2300-amino acid protein (theoretical molecular mass = 264 kDa; isoelectric point = 6.22), and no putative si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…ChamQTM SYBR ® qPCR Master Mix (Vazyme, Nanjing, China) was used in real-time quantitative PCR. The average cycle thresholds (Ct) were calculated by using 2-∆∆CT method which was used to calculate relative gene expression levels [55]. The primers for HSP47: 5 -ACC GAG CCC TCT TCA GTC TT-3 (Forward), 5 -GGT GAT GCC CAA CAT AAC AAT-3 (Reverse).…”
Section: Quantitative Real Time-pcrmentioning
confidence: 99%
“…ChamQTM SYBR ® qPCR Master Mix (Vazyme, Nanjing, China) was used in real-time quantitative PCR. The average cycle thresholds (Ct) were calculated by using 2-∆∆CT method which was used to calculate relative gene expression levels [55]. The primers for HSP47: 5 -ACC GAG CCC TCT TCA GTC TT-3 (Forward), 5 -GGT GAT GCC CAA CAT AAC AAT-3 (Reverse).…”
Section: Quantitative Real Time-pcrmentioning
confidence: 99%
“…CHS gene from freshwater pearl mussel H. cumingii was sequenced using a molecular cloning technique, revealing the presence of myosin head domain (Zheng et al, 2015). Myosin motor head domain function was predicted to be inhibiting the mineralization process and thereby regulating the chitin deposition.…”
Section: Chitin Synthesis Via Genomic Pathwaymentioning
confidence: 99%
“…Phylogenetic analysis revealed that CHS genes of most crustacean species were clustered together and more specific to arthropods closely related to insects (Zhang et al., 2021). This made them distant from mollusk CHS (Zheng et al., 2015). Further phylogenetic analysis revealed that the CHS gene of mollusk Hyriopsis cumingii , Pinctada fucata , Atrina rigida , and Mytilus galloprovincialis were similar in identity.…”
Section: Chitin Synthesis Via Genomic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Perlucin is another important matrix protein of H. cumingii that is believed to induce pearl formation (Lin et al, 2013). Studies into the recently cloned HcCS1 gene have demonstrated its important role in shell formation via the regulation of chitin synthesis (Zheng et al, 2015). Silkmapin is another new matrix protein that has been shown to participate in the nucleation of calcium carbonate, providing nucleation sites to facilitate nacre formation .…”
Section: Introductionmentioning
confidence: 99%